Allughah al-‘Arabiyyah fi Indonesia Madiha , Hadhiriha, wa Mustaqbaliha - bachmid, ahmad (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2017)
AbstractThis article discusses about the spread of Arabic in Indonesia, which is divided into three lines of time; that is (1) the past, (2) the present and (3) the future. Core questions to be answered through this article is describing how the initial entry of Islam in Indonesia, because the religion of Islam was identical with the Arabic language. The Holy Book (the Koran) using the Arabic language, as well as Hadith. Arabic is the language of worship especially prayer. The inclusion of Islam into Indonesia played by Arab merchants in the process of Islamization in Indonesia. Then in the 15th century, namely (1) the development of the Arabic language is portrayed by the Wali Songo by developing boarding school-boarding school with their slogan, that focus on mastery of the Arabic language. At the beginning of this, teaching pesanteren system focused on reading the books of the original yellow speak Arabic as a medium. Then came the time of (2) driven by the return of alumni of the Islamic universities its founders came from the Middle East who was played by Pesanteren of modern educational system with the Gontor modern. And (3) Arabic already vibrant dijarkan madrasah ibtidaiyah in madrasah tsanawiyah,-, aliyah and at universities – the University of Islam and is common in Indonesia, there is even a special status-status of the study of the Arabic language. — AbstrakArtikel ini membahas tentang penyebaran bahasa Arab di Indonesia, yang terbagi dalam tiga garis waktu; yaitu (1) masa lalu, (2) masa sekarang dan (3) masa depan. Pertanyaan inti yang harus dijawab melalui artikel ini adalah menggambarkan bagaimana masuknya Islam awal di Indonesia, karena agama Islam identik dengan bahasa Arab. Kitab Suci (Alquran) menggunakan bahasa Arab, juga hadits. Bahasa Arab adalah bahasa ibadah terutama doa. Masuknya Islam ke Indonesia dimainkan oleh para pedagang Arab dalam proses islamisasi di Indonesia. Kemudian pada abad ke 15, yaitu (1) perkembangan bahasa Arab dilukiskan oleh Wali Songo dengan mengembangkan pesantren dengan slogan mereka, yang fokus pada penguasaan bahasa arab. Pada awal ini, pengajaran sistem pesanteren terfokus pada pembacaan buku-buku bahasa asli berwarna kuning berbahasa Arab sebagai media. Kemudian datanglah waktu (2) yang didorong oleh kembalinya alumni universitas Islam para pendirinya berasal dari Timur Tengah yang diperankan Pesanteren dari sistem pendidikan modern dengan modern Gontor. Dan (3) bahasa Arab sudah semarak dijarkan madrasah ibtidaiyah di madrasah tsanawiyah, -, aliyah dan di universitas - Universitas Islam dan umum di indonesia, bahkan ada status status khusus dari studi bahasa arab.DOI : 10.15408/bat.v23i2.6372